2021
DOI: 10.1017/s0029665121001968
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient malnutrition across the life course, sarcopenia and frailty

Ailsa Welch

Abstract: Micronutrient malnutrition, the deficiency of vitamins or minerals, impacts on physical and mental health, in clinical and general populations, across the life course. In older western populations the high prevalence and impact of micronutrient malnutrition is less well recognised. Low- and middle-income countries are experiencing the ‘double burden of disease’ where malnutrition coexists alongside the non-communicable diseases of aging, obesity, type 2 diabetes and cardiovascular disease. Held in December 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Lack of good quality food in the right quantity coupled with anabolic resistance [ 18 , 19 ] can ultimately result in protein and micronutrient undernutrition. The clinical consequences of this can manifest as frailty, sarcopenia, and an ineffective immune system with an increase in morbidity and eventual death [ 19 , 20 ].…”
Section: Nutritionmentioning
confidence: 99%
“…Lack of good quality food in the right quantity coupled with anabolic resistance [ 18 , 19 ] can ultimately result in protein and micronutrient undernutrition. The clinical consequences of this can manifest as frailty, sarcopenia, and an ineffective immune system with an increase in morbidity and eventual death [ 19 , 20 ].…”
Section: Nutritionmentioning
confidence: 99%
“…The progression of sarcopenia or frailty is associated with the risk and prevalence of several diseases, including cardiovascular diseases, dementia, and fractures [ 6 , 7 , 8 ]. Concerning the role of nutrition in the progression of sarcopenia and frailty, epidemiological studies have highlighted the roles of nutrients such as proteins, essential amino acids, omega-3 fatty acids, and vitamin D in the context of sarcopenia, frailty, and survival [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, older persons are more susceptible to protein-energy and micronutrient malnutrition. Of these, the consequences of micronutrient deficiencies are sometimes permanent ( 14 ). Epidemiological studies have shown a correlation between micronutrients and frailty.…”
Section: Introductionmentioning
confidence: 99%